PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP KEMAMPUAN LITERASI MEMBACA SISWA SD - Nur Johan; Haifaturrahmah; Nursina Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the influence of using interactive learning media on elementary students’ reading literacy skills. Reading literacy is a fundamental skill that plays a crucial role in supporting students’ academic success across various disciplines. However, the low level of reading literacy among elementary students remains a challenge, mainly due to the dominance of conventional teaching methods that fail to engage students actively in the learning process. To address this issue, this research employed a qualitative descriptive approach involving teachers and students who have used interactive learning media in reading activities. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of interactive learning media has a positive impact on improving students’ reading literacy skills. The integration of text, images, audio, and animation in interactive media creates a more engaging, participatory, and meaningful learning environment. Students become more motivated, active, and better able to comprehend reading materials both literally and inferentially. Moreover, interactive media enriches vocabulary, enhances critical thinking, and strengthens analytical and evaluative reading skills. Teachers also perceive that the use of interactive media not only improves reading comprehension but also fosters collaboration and discussion among students during literacy activities. Therefore, interactive learning media proves to be an effective tool for enhancing reading literacy while cultivating a positive attitude toward reading among elementary school students.Kata Kunci: Interactive Learning Media, Reading Literacy, Elementary Students, Learning Motivation, Digital Learning